Association between domestic violence and oral health conditions among adolescents (Research, Society and Development, 2021)
This study surveyed the oral health conditions of adolescents aged 15 to 19 years and their association with exposure to domestic violence. The study sample consisted of 333 adolescents enrolled in the State School System in the city of Olinda, PE, Brazil. Sociodemographic data, information on the participant’s oral health conditions, and their history of domestic physical violence were collected. The health-related variables analyzed included self-perceived oral health, history of toothache, and the frequency of toothbrushing and visits to the dentist. The data were entered into the Epi data 3.1 and analyzed in the SPSS program 23.0 by Pearson's Chi-square or Fisher's exact tests. There was a significant association of history of toothache and domestic violence with physical aggression from the mother (P = 0.001; OR = 2.39), a relative (P = 0.001; OR = 2.41) and any family member and/or with witnessing violent acts between the parents (P = 0.011; OR = 1.88). However, no association between physical violence and self-perceived oral health or the frequency of visits to the dentist was observed. To conclude, our findings indicate that the oral health conditions of adolescents may be directly associated with domestic violence.